추출용매 및 발아시기에 따른 무순 추출물의 생리활성 비교 - 한진희(Jin-Hee Han); 문혜경(Hye-Kyung Moon); 정신교(Shin-Kyo Chung); 강우원(Woo-Won Kang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
This study extracted radish bud (Raphanus sativus L.) and investigated its nitrite scavenging activity, superoxide dismutases (SOD)-like activity, tyrosinase inhibition activity, xanthine oxidase inhibition activity, and angiotensin-converting-enzyme (ACE) inhibition activity according to extraction solvent and sprouting period. For nitrite scavenging activity, each extract recorded its highest level of 81.44~89.71% at pH 1.2. Radish bud extracts on sprouting days 4 and 8 showed greater scavenging activities than those on sprouting day 12 at pH 1.2 and pH 4.0. There were differences in scavenging activity according to extraction solvent based on water extract exhibiting improved scavenging activity. Ethanol extract recorded scavenging activity of 16.12% at pH 6.0, which was similar to those of ethanol and methanol radish bud extracts on sprouting day 12. SOD-like activity of radish bud extracts was in the range of 4.57~27.05%. For comparison purposes, SOD-like activity of L-ascorbic acid was 52.15%, which was higher than that of radish bud extracts. Acetone and methanol extracts showed high SOD-like activities on sprouting day 8. SOD-like activity of radish bud extracts on sprouting day 12 significantly decreased to 4.57~15.59%. Radish bud extracts recorded good tyrosinase inhibitory activities on sprouting 8 and 12, whereas methanol extracts recorded the greatest tyrosinase inhibitory activity at 62.65~84.89%. Radish bud extracts recorded xanthine oxidase inhibition activity of 21.26~29.52% on sprouting day 4, and acetone extracts showed the highest level of xanthine oxidase inhibition activity. Xanthine oxidase inhibitory activity tended to decrease with sprouting period compared early on. ACE inhibitory activity was in the range of 12.48~51.78% according to sprouting period and extraction solvent. Ethanol extracts on sprouting day 8 showed the highest ACE inhibitory activity of 51.78%. These results will hopefully contribute to research into the identification of materials and development of products for natural functional foods. 본 연구에서는 무순을 추출용매 및 발아시기에 따라 추출하여 아질산염 소거능, SOD 유사 활성, tyrosinase 저해 활성, xanthine oxidase 저해 활성 그리고 ACE 저해 활성을 측정하였다. 아질산염 소거능 측정에서는 pH 1.2의 Z2조건에서 각 추출물들이 81.44~89.71%로 가장 높은 소거능을 나타내었고 pH 1.2와 pH 4.0의 조건에서 발아 4일째와 8일째의 무순 추출물이 발아 12일째의 무순 추출물보다 높은 소거능 효과를 나타내었다. 또 추출용매에 따라 소거능의 차이는 보였으나 물로 추출한 추출물이 상대적으로 다른 용매 추출물에 비해 소거능 효과가 좋은 것으로 나타났다. pH 6.0 조건에서는 에탄올 추출물이 16.12%의 활성을 보여 발아 12일째 무순의 에탄올 추출물과 메탄올 추출물의 소거능 효과와 유사한 결과를 보였다. 무순 추출물의 SOD 유사 활성은 4.57~27.05%의 범위를 보였고 비교물질인 L-ascorbic acid의 활성이 52.15%로 무순 추출물의 활성보다 높은 것으로 나타냈다. 추출물 중에서는 발아 8일째의 아세톤 추출물과 메탄올 추출물의 활성이 높은 것으로 나타났고 발아 12일째의 무순 추출물의 SOD 유사 활성은 4.57~15.59%로 현저히 감소하는 것으로 나타났다. Tyrosinase 저해 활성은 발아 8일째와 12일째의 무순 추출물의 활성이 좋았으며, 추출용매는 메탄올 추출물이 62.65~84.89% 측정되어 가장 좋은 저해 활성을 보였다. Xanthine oxidase 저해 활성은 발아 4일째의 무순 추출물이 21.26~29.52%로 아세톤 추출물이 가장 높은 저해능을 나타내었고 발아초기에 비해 발아가 진행됨에 따라 저해능은 감소하는 경향을 나타내었다. 발아시기와 추출용매에 따른 ACE 저해능은 12.48~51.78%의 저해 활성을 보였으며, 발아 8일째의 에탄올 추출물이 51.78%로 각 추출물 중 가장 높은 저해 활성을 보였다. 이와 같은 생리활성 결과를 기초로 하여 천연 기능성 식품의 소재 발굴 및 식품 개발에 있어 연구 활용의 가능성이 있을 것으로 기대되며 일반적으로 섭취하여 큰 효능을 기대하기 어려운 무순을 유효성분만을 추출하여 소재화 하는 것이 더 효율적이라고 판단된다. 또한 현행 건강기능식품법에 따르면 물, 주정, 핵산 등의 추출용매를 사용하여 유효성분을 추출하는 것을 허용하고 있으므로 용매의 종류 및 추출방법에 대한 추가적인 연구를 통해 큰 기대 효과를 줄 수 있을 것이라 생각된다.